2020
DOI: 10.3168/jds.2020-18339
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and nongenetic profiling of milk β-hydroxybutyrate and acetone and their associations with ketosis in Holstein cows

Abstract: Ketosis is a metabolic disorder of increasing importance in high-yielding dairy cows, but accurate population-wide binary health trait recording is difficult to implement. Against this background, proper Gaussian indicator traits, which can be routinely measured in milk, are needed. Consequently, we focused on the ketone bodies acetone and β-hydroxybutyrate (BHB), measured via Fourier-transform infrared spectroscopy (FTIR) in milk. In the present study, 62,568 Holstein cows from large-scale German co-operator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 62 publications
(75 reference statements)
2
11
0
1
Order By: Relevance
“…After imputation to WGS, an additional QC was performed to remove the individuals and SNPs with a missing rate greater than 0.1, minor allele frequency (MAF) lower than 0.01, and extreme deviation from Hardy-Weinberg equilibrium (p < 10 −8 ; e.g., [41][42][43]. Finally, a range of 5,108,861 to 6,101,357 SNPs remained for the GWAS analyses of LP and milk production traits.…”
Section: Iwgs and Genomic Quality Controlmentioning
confidence: 99%
“…After imputation to WGS, an additional QC was performed to remove the individuals and SNPs with a missing rate greater than 0.1, minor allele frequency (MAF) lower than 0.01, and extreme deviation from Hardy-Weinberg equilibrium (p < 10 −8 ; e.g., [41][42][43]. Finally, a range of 5,108,861 to 6,101,357 SNPs remained for the GWAS analyses of LP and milk production traits.…”
Section: Iwgs and Genomic Quality Controlmentioning
confidence: 99%
“…( 2018 ) observed a repeatability of 0.20 for BHB, whereas Klein et al. ( 2020 ) reported values lower than 10% due to small PE variances (genomic‐based). Repeatability estimates closer to the ones in the present study were found in the literature for blood BHB: Benedet et al.…”
Section: Resultsmentioning
confidence: 99%
“…Luke et al (2019) reported genomic-based h 2 of 0.09 ± 0.04 for BHB LOG10 measured within 30 days after calving in 1,393 Holstein-Friesian Australian cows. Benedet et al (2018) observed a repeatability of 0.20 for BHB, whereas Klein et al (2020) reported values lower than 10% due to small PE variances (genomic-based). Repeatability estimates closer to the ones in the present study were found in the literature for blood BHB: Benedet et al (2020) reported r 2 of 0.26 ± 0.01 in early-lactation (up to 35 days in milk) Holstein cows (pedigree-based).…”
Section: Variance Components and Heritabilitiesmentioning
confidence: 99%
“…The genome-wide significance level according to Bonferroni was 1.22 × 10 −6 (pBonf = 0.05/N SNP = 40,824). In addition, we considered a less conservative suggestive significance candidate threshold (pCand = 1 × 10 −4 ) according to Kurz et al (2019) and Klein et al (2020). Potential candidate genes were queried and assigned to the associated SNP using the ENSEMBL database based on the Bos taurus ARS-UCD1.2 genome assembly (Yates et al, 2020).…”
Section: Effects Of Uterine Diseases On 305-d Lactation and Fertilitymentioning
confidence: 99%